Comparison among Early-Onset, Late-Onset, and Conventional-Onset Adenocarcinoma of Stomach and Esophagogastric Junction: a Retrospective Study - Yidi Liang; Kai Liu; Valentin Kudriashov; Lifei Sun; Weihan Zhang; Xiaolong Chen; Linyong Zhao; Xiaohai Song; Kun Yang; Jiankun Hu (World Journal of Surgical Oncology)
Abstract Background The incidence of EOGC has been increasing, while COGC has decreased over the past few decades. The objective of this study was to identify differences in clinical characteristics and prognosis and to verify survival results among early-onset gastric cancer (EOGC), conventional-onset gastric cancer (COGC), late-onset gastric cancer (LOGC), and within the adenocarcinoma of the esophagogastric junction (AEG) group. Materials and Methods A retrospective trend analysis was conducted on patients diagnosed with gastric adenocarcinoma between 2002 and 2021. Additionally, 3,940 patients who underwent radical gastrectomy between January 2009 and December 2019 were included in a further analysis. The patients were categorized into three groups based on their age: EOGC, COGC, and LOGC. The study compared the three groups' demographic parameters, surgical details, pathological characteristics, and survival rates. Results From 2002 to 2021, there was a fluctuating decrease in the surgical population of EOGC from 18.0% to 9.4% (p < 0.0001). 3940 patients were included in this analysis, EOGC (n = 572), COGC (n = 2816), and LOGC (n = 552). The EOGC group indicated a higher proportion of females (p < 0.0001), poorer differentiation p < 0.0001), higher proportion of signet-ring cell cancer (SRCC) (p < 0.0001), and lower Her-2 expression (p = 0.0038) than the COGC and LOGC groups. EOGC patients showed the best overall survival rate compared to COGC (p = 0.0110) and LOGC (p < 0.0001). After stratified by TNM stage, LOGC patients had the worst survival among all stages. When considering the patients with AEG, the EOGC group showed the worst survival outcome (p = 0.0130). Only patients with COGC showed improved survival with chemotherapy compared to those without it (stage II: p = 0.0051; stage III: p = 0.0160). Conclusion A decreasing trend in the EOGC surgical population has been observed over the past 20 years at West China Hospital. Compared to COGC patients, EOGC patients had a higher proportion of females, SRCC cases, poorer differentiation, and lower Her-2 expression, but demonstrated a better survival outcome. Conversely, the worst prognosis outcome was observed in EOGC patients within the AEG subgroup. LOGC was an independent negative factor for survival results. Chemotherapy did not improve the prognosis for EOGC and LOGC patients at stage II and III.